Pelatihan dan Pendampingan Pengelolaan Sampah Organik Menjadi Kompos Dengan Metode Takakura di Desa Waduwani - Ika Irawati; Nur Fitrianingsih; Sri Yanti; Ihsan Ihsan; Deddy Meirawan (Jurnal Gema Ngabdi, 2021)
Garbage have been become big problem for our environment, especially the garbage at Waste Processing Site (TPA) on Waduwani Village. Several efforts have been made by government to reduce garbage volume. But these efforts have not been fully realized in the community. So that it is urgently needed an appropriate and comprehensive solution to reduce the volume of the garbage and its negative effect on environment. Training and assistance to make organic garbage to be the compost by using “Takakura method” is the one solution to reduce garbage problems. This activity is a Community Service for the community, especially women in Waduwani village, Woha sub-district of Bima, NTB. The objectives of this community service activity includes (1) Counseling the community to improve community knowledge and skills to make organic garbage properly and sustainably. (2) The management and training can reduce the volume of organic garbage generated from the house. (3) The results of training of compost made can be utilized by the community, especially to fertilize their plants. The method of implementing this activity is carried out in four stages, namely; socialization, Implementation program, Garbage processing, and finally Program evaluation. The results of Takakura Method are (1) IncreaseMothers knowledge and skills to manage the garbage (2) Reduce the garbage volume which generated at household/kitchen. (3) The results of make Takakura compost can be used directly by mothers to fertilize their plants.